Characterization of gut lipases in Helicoverpa armigera: New insights into the role of intracellular lipases in cholesterol homeostasis - Zhen Yang; Haoyu Tan; Xiaoqing Yang; Yuling Zhang; Junhao Liang; Wenqing Kuang; Zhanfeng Zhang; Tong-Xian Liu; Xiangfeng Jing (Insect Biochemistry and Molecular Biology, 2026)

Characteristics and source apportionment of atmospheric fine particulate-bound mercury (PBM2.5) in abandoned mercury mining areas in southwestern China - Yuling Kuang; Longchao Liang; Shasha Liu; Xian Dong; Fang Zhu; Xiaohang Xu; Zhuo Chen; Yayun Li; Yaji Li; Guangle Qiu (Acta Geochimica, 2026)

Mercury dynamics and speciation in paddy soils irrigated with acid mine drainage from abandoned coal mine: Insights from vertical profiling - Shasha Liu; Longchao Liang; Xiaohang Xu; Yuling Kuang; Le Wang; Guangle Qiu; Zhuo Chen; Xian Dong; Jialiang Han (Acta Geochimica, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Review: Specific storage in aquitards - Yinong Cai; Yuling Yin; Xingxing Kuang; Yinlei Hao; Junguo Liu; Chunmiao Zheng (Hydrogeology Journal, 2023)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)